Keeping it Clean: Cleaning the Kitchen Stove, Range Top, and Oven - Mary N. Harrison (EDIS)
A clean kitchen is a “must.” It is very important to the health of your family. This document is FCS5232-05, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date June 2002. Revised December 2005.